Legal Analysis Of Compensation Lawsuits Due To The Cancellation Of Unilateral Marriage Promises (Case Study of Supreme Court Decision No. 1644 K/Pdt/2020) - Obviarezqi, Alfrida (UMPurwokerto Law Review, 2022)
Abstract Marriage promises made by a man to a woman are usually only verbal without written evidence. If the party who made the promise denies it, holding him accountable will not be easy, so this situation is very detrimental to women, both material and immaterial losses. The objectives of this study are to identify and criticize the cancellation of a marriage promise as an act against the law or default and to find out what are the legal consequences that arise from an act of unilaterally canceling a marriage promise. This research is normative juridical research, essentially examining the law conceptualized as a norm or rule that applies in society and becomes a reference for everyone’s behavior. This study emphasizes secondary data, which emphasizes the study of positive legal principles derived from library data, which means it will examine and examine secondary data as a normative approach. The research specification used is descriptive-analytical, namely by describing the applicable laws and regulations related to legal theories and positive law implementation practices related to problems. The cancellation of a marriage promise carried out unilaterally is included in an unlawful act; the consequences arising from the cancellation of a unilateral marriage promise are material or immaterial losses. Keywords: Promise of Marriage, Acts against the law, default Abstrak Janji kawin yang diucapkan oleh seorang laki â€“ laki pada perempuan biasanya hanya secara lisan tanpa adanya bukti tertulis. Jika pihak yang berjanji mengingkarinya, maka akan sulit untuk meminta pertanggungjawabannya. Sehingga keadaan ini sangat merugikan bagi pihak perempuan baik kerugian materiil maupun kerugian immateriil. Tujuan yang ingin dicapai dari penelitian ini adalah untuk mengetahui dan mengkritisi pembatalan janji kawin merupakan perbuatan melawan hukum atau wanprestasi dan untuk mengetahui apa akibat hukum yang timbul dari suatu perbuatan pembatalan janji kawin sepihak. Penelitian ini merupakan penelitian yuridis normatif, pada hakikatnya mengkaji hukum yang di konsepkan sebagai norma atau kaidah yang berlaku dalam masyarakat, dan menjadi acuan perilaku setiap orang. Penelitian ini menekankan pada data sekunder yang menekankan kajian pada asas-asas hukum positif yang berasal dari data kepustakaan yang berarti akan meneliti dan mengkaji data sekunder sebagai pendekatan normatif. Spesifikasi penelitian yang digunakan adalah deskriptif-analitis, yaitu dengan menggambarkan peraturan perundang-undangan yang berlaku dikaitkan dengan teori-teori hukum dan praktek pelaksanaan hukum positif yang berkaitan dengan permasalahan. Pembatalan janji kawin yang dilakukan secara sepihak termasuk dalam perbuatan melawan hukum, akibat yang timbul dari adanya pembatalan janji kawin sepihak yaitu adanya kerugian materiil maupun immateriil. Kata kunci: Janji Kawin, Perbuatan melawan hukum, wanprestasi